How does agomelatine affect contraction in rat myocardial tissue? - Özen Koca, Raviye; Solak Görmüş, Zülfikare Işık; Solak, Hatice; Akdoğan, Gülnur (The European Research Journal, 2025)
Objectives: Cardiovascular diseases and depression are frequently seen together. Despite the developments in the treatment efficacy of agomelatine, a widely used antidepressant, its safety profile on cardiac tissue has not been sufficiently investigated. The aim of this study was to evaluate effects of agomelatine on contraction in rat myocardial tissue in depression and anxiety conditions frequently encountered in cardiovascular diseases and after cardiac surgery. Methods: Myocardial tissue sections were removed from 12 male Wistar Albino rats divided into control and agomelatine groups. The tissues were placed in the isolated organ bath system. Maximum contraction was achieved by applying 10-1 M adrenaline to both groups. When the contraction plateaued, the same volume of vehicle as agomelatine were applied to the Control group. Agomelatine cumulative doses (10-8 – 10-4 M) were applied to the agomelatine group. The resulting isometric contraction forces were recorded by the isolated organ bath system. The statistical analyses of the study were performed with the R 4.3.1 program. Results: A significant increase in the tension of the tissues was observed with adrenaline in both the Control and Agomelatine groups. In the Agomelatine group, the tension at 10-8 agomelatine dose was significantly lower compared to 10-1 M adrenaline dose (P<0.05), and tension at 10-6 agomelatine dose was significantly lower compared to 10-7 agomelatine dose (P<0.05). Conclusions: Agomelatine produced a dose-dependent suppressed contractile response in myocardial tissue. This suggests that it may have positive effects on increased blood pressure, positive inotropic effect and hypertensive state, which can occur in cardiovascular diseases and are also common in depression. Agomelatine may have a more favorable side effect profile than other antidepressants in cardiovascular disease states.